Collaborating for change: reimagining medical education in Jordan through international partnerships - Mahmoud M. Sarhan; James Kelly; Neveen El-Farra; Mohammed Ahmed Rashid (Discover Education)
Abstract Medical education in Jordan has evolved rapidly in the last 50 years as successive governments and higher education leaders have responded swiftly to developing healthcare sector demands. Despite significant progress being made, there remain a substantial number of challenges for the Jordanian medical education system that require careful attention in the years and decades ahead. This article provides a historical summary of medical education in Jordan, outlines some of the important areas that require development, and describes plans for a new medical school and teaching hospital in Amman at the newly established Kingdom University of Health Sciences, due to open in 2026. This ambitious project is being funded by the Saudi Jordanian Investment Fund and is being supported by partnerships with high-ranking, well-established institutions in the UK and USA. This article highlights the significant value in a partnership approach to developing a medical education program as it strives to overcome some of the existing challenges facing medical education in Jordan.